Penerapan Strategi Pembelajaran Contextual Teaching and Learning Dalam Meningkatkan Aktivitas dan Hasil Belajar IPA Terpadu Siswa SMP Negeri 2 Mandrehe Barat Tahun Pembelajaran 2024/2025 - Efiktor Manuel Gulo; Jun Mardin Telaumbanua; Ester Novi Kurnia Zebua (Program Studi Pendidikan Biologi - Universitas Nias, 2025)
The main problem in this study is the low activity and learning outcomes of students in Integrated Science subjects at SMP Negeri 2 Mandrehe Barat, where the average student score is still below the Minimum Completion Criteria set by the school, namely 55.2. The purpose of this study is to describe the learning process, student learning activities, and student learning outcomes after implementing the Contextual Teaching and Learning strategy. This classroom action research was conducted in class VIII-B semester 1 with a total of 22 students through two learning cycles. The first cycle discussed the material on the human locomotor system while the second cycle discussed the human digestive system. The instruments used included observation sheets for active and inactive students, observation sheets for learning activities, learning outcome tests, and documentation in the form of photos. The results of the study showed a significant increase in all measured indicators. Teacher respondent observations increased from 80.14 percent in cycle I to 92.64 percent in cycle II. Student learning activities increased from 62.90 to 96.75, while student learning outcomes improved from an average of 67.28 with a completion rate of 60.52 percent to 80.67 with a completion rate of 92.10 percent. Significant findings indicate that the implementation of the Contextual Teaching and Learning strategy is effective in improving the quality of Integrated Science learning.